The Application of Restful Web Service and Json for Poultry Farm Monitoring System - Hindriyanto Dwi Purnomo; Dody Agung Saputro; Ramos Somya; Charitas Fibriani (JEECS (Journal of Electrical Engineering and Computer Sciences), 2016)
Partnership schema is widely applied in Indonesia poultry farm industry. In this schema, a poultry company cooperates with many breeder partners to raise their chicken. The company sends their field inspection staffs to monitor the growth of the chickens. Large number of breeders with manual process of report, handle, and monitor takes a significant amount of time and efforts. In addition, the data cannot be observed immediately by the company. A poultry farm monitoring system based on the Application Programming Interface (API) is proposed in this research. The system can be used by breeders, breeder partners and field inspection staffs to facilitate the process of reporting, handling and monitoring by the poultry company. The API technology is applied as a data center and a data provider. The combination of RESTful web service and JSON into the API enable the integration can be processed safely as well as simple and easy to use. The proposed system can be applied to complement or replace the existing manual processes on many poultry farms with partnership schema.